Physiological and morphological mechanisms regulating blossom-end rot in tomato fruits - Riboldi, Lucas Baiochi (2018)
Ca2+ is a nutrient for plant development, and its deficiency causes poor cellular development in tomato fruits, resulting in a physiological disorder known as blossom-end rot (BER). Studies on this physiological disorder are not recent and mainly focused on Ca2+ deficiency in tissues and on the interaction between plant and the environment. However, new research has been based on hormonal interaction and oxidative mechanisms in fruits. Hormones such as gibberellins, abscisic acid, and brassinosteroids have been implicated in both activation and inhibition of BER symptoms. The application of abscisic acid and epibrasinolide decreased fruit susceitibility to BER. Abscisic acid reduces leaf transpiration, inhibiting xylem sap and calcium flow into the leaves and increasing into the fruit. Epibrassinolide increased fruit antioxidant responses, decreasing hydrogen peroxide and increasing ascorbic acid content, as well as increasing ascorbate peroxidase, catalase, and superoxide dismutase activities. In addition, the selection of varieties more tolerant to BER and the identification of factors that make new varieties resistant are important tools in the selection of new varieties. In this study, many varieties were evaluated in order to understand the relationship between fruit shape and growing environment on BER incidence in the fruit. According to the results, elongated fruit varieties showed higher susceptibility to BER.